Caracterização tecnológica da madeira de Acacia mearnsii De Wild. para a produção de polpa celulósica Kraft - Giesbrecht, Bruna Mohr (2017)
The Acacia mearnsii De Wild. is widely cultivate for the tannin extraction of its bark, while the wood, exported to the Asian countries, can be converted in cellulosic pulp. Although the efficiency of this wood on pulping is proved, in Brazil the specie is rarely used for this purpose. Thus, the aim of this work was to characterize technologically the Acacia mearnsii wood, trough chemical, anatomical and basic density analysis, and evaluate the cellulosic pulp quality, produced by the kraft process. It was collected ten trees, five from a seed production area (APS) and five from clonal plantations, which were felled and divided in discs and prepared in accordance with TAPPI T264 om-88 standart. The basic density was performed in accordance with NBR 11941 (2003) standart, and the wood description was set trough the preparation of histological slides and of macerated, according to Burger and Richter (1991) and by the nitric-acetic method, respectively, followed by anatomical measurements on microscope. It was performed quantitative analysis of the chemical components, besides the syringyl/guaiacyl ratio and the total carbohydrates content by high efficiency liquid chromatography. The kraft pulps were carried out only in APS chips, keeping constant the time, sulfidity and the temperature of cooking, changing just the active alkali charge, which ranged from 14 to 24%. In cellulosic pulps, it was evaluated the yields, kappa number and rejects content, besides the analysis of solid content in black liquor. The basic density results showed that Acacia mearnsii wood from APS and clones did not presented significant difference, with values of, approximately 0,544g/cm³. In wood description, the anatomical elements presented values much similar to the genre Eucalyptus sp., with thin to thick wall fibers (± 3,3 μm) and anatomical indices indicating suitable fibers for paper production. The chemical analysis revealed an ashes content of, approximately 0,35%, total extractives of 4,5 to 4,8%, Klason lignin of 16,2 to 17,1%, holocellulose and alpha-cellulose of 76 to 77% and 46%, respectively. The glucose content was 51,7 and 49,7% for clone and APS, while the hemicelluloses (xylose, arabinose, mannose and galactose) totaled circa 19%. The S/G ratio was 2,69 and 2,93 in clone and APS, respectively. The pulps made with different charges of active alkali presented satisfatory yields and kappa numbers. The best pulping condition was obtained with active alkali of 14%, resulting in a screened yield of nearly 57%, kappa number of 16, rejects content of ± 0,2% and solids content of 12,7%. According with the results, the Acacia mearnsii wood presents a great potential as a source of short fibers in cellulosic pulp production.